Public-Private Collaboration to Overcome the Digital Divide in Digital Transformation of Government - Younus, Muhammad; Suswanta; Muchamad Zaenuri (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2024)
The objective of this article is to explore the issue of the digital divide and how we can bridge it to overcome the challenge of digital transformation. We will start by examining the key factors that contribute to the issue of the digital divide, which include economic factors, accessibility of infrastructure and technology, and also digital literacy. We will explore the strategies and initiatives that need to be implemented to address these challenges and promote digital inclusion. Based on our research, we have argued that bridging the digital divide is not only limited to social justice and equity but is also a key driver for achieving economic growth and innovation. We will focus on how important it is to ensure that every citizen can access digital services equally. Also, they should be trained with the skills to use it effectively. Public-private collaboration is essential for bridging the digital divide in government digital transformation. This study identifies key strategies and outcomes of such collaborations, emphasizing their role in enhancing digital access and service delivery. Findings underscore the importance of partnership models in fostering inclusive and effective digital governance. So, overall, this article will provide a comprehensive overview of the digital divide, its challenges, and how we can solve these problems to create opportunities that will add value to the country's progress.